In vivo implementation of a synthetic metabolic pathway for the carbon-conserving conversion of glycolaldehyde to acetyl-CoA - Wagner, Nils; Bade, Frederik; Straube, Elly; Rabe, Kenny; Frazão, Cláudio J. R.; Walther, Thomas (Frontiers in Bioengineering and Biotechnology, 2023)
Ethylene glycol (EG) derived from plastic waste or CO2 can serve as a substrate for microbial production of value-added chemicals. Assimilation of EG proceeds though the characteristic intermediate glycolaldehyde (GA). However, natural metabolic pathways for GA assimilation have low carbon efficiency when producing the metabolic precursor acetyl-CoA. In alternative, the reaction sequence catalyzed by EG dehydrogenase, D-arabinose 5-phosphate aldolase, D-arabinose 5-phosphate isomerase, D-ribulose 5-phosphate 3-epimerase (Rpe), D-xylulose 5-phosphate phosphoketolase, and phosphate acetyltransferase may enable the conversion of EG into acetyl-CoA without carbon loss. We investigated the metabolic requirements for in vivo function of this pathway in Escherichia coli by (over)expressing constituting enzymes in different combinations. Using 13C-tracer experiments, we first examined the conversion of EG to acetate via the synthetic reaction sequence and showed that, in addition to heterologous phosphoketolase, overexpression of all native enzymes except Rpe was required for the pathway to function. Since acetyl-CoA could not be reliably quantified by our LC/MS-method, the distribution of isotopologues in mevalonate, a stable metabolite that is exclusively derived from this intermediate, was used to probe the contribution of the synthetic pathway to biosynthesis of acetyl-CoA. We detected strong incorporation of 13C carbon derived from labeled GA in all intermediates of the synthetic pathway. In presence of unlabeled co-substrate glycerol, 12.4 % of the mevalonate (and therefore acetyl-CoA) was derived from GA. The contribution of the synthetic pathway to acetyl-CoA production was further increased to 16.1 % by the additional expression of the native phosphate acyltransferase enzyme. Finally, we demonstrated that conversion of EG to mevalonate was feasible albeit at currently extremely small yields.